A crack in the Swedish welfare façade? A review of assessing social impacts in transport infrastructure planning. (May 2020) - Antonson, Hans; Levin, Lena
Highlights: Social issues, considered but poorly integrated in EIA reports, are deteriorating.. New EIA manuals and working routines would strengthen social issues in EIA.. Deficient interplay regarding social issues in EIA calls for actor networks.. Sweden ignores social impact categories in transport infrastructure development.. Policy documents and government bills indicate a gap between theory and practice.. Abstract: A comparison of social impact categorisation in strategic planning across European Union Member States shows that Sweden neither categorises nor breaks down categories of social impact in areas such as transport infrastructure development. This is surprising because Sweden is known as a country concerned about social issues and having a high standard of welfare. This article accordingly studies how social issues are handled during transport infrastructure planning. An analysis of different source materials will answer four research questions: 1) To what extent are social impacts integrated into environmental impact assessment (EIA) reports? 2) Are social impacts sufficiently integrated and/or does this treatment simply amount to 'good practice'? 3) Can any trend be detected over time in terms of addressing social issues in impact assessments? 4) What key measures could increase the influence of social impact issues on transport infrastructure planning practice? The study involved a content analysis of six EIA handbooks and EIA statements (EISs) for 18 large transport infrastructure projects. The concepts searched for in these documents largely apply to issues of vulnerability, health, social problems, perceived safety, and alienation. Our data were interpreted through the theoretical lens of institutional interplay. We found that though social aspects are not new considerations in EIA research, they are included in only a small proportion of the 18 Swedish EISs, mostly in connection with health and accessibility. We believe that this does not suffice. We also found that the more recent documents allotted less space to social issues. It is unlikely that most individuals in the organisations that order EISs, or the consultancies that write them, are unaware of the broader interpretation of 'human beings' which includes social aspects. Based on increasing interest in social issues in planning and due to the lack of national goals and guidelines in this area, some municipalities and consultants have begun to create their own methods of measuring and assessing social impacts. This has resulted in multiple local-level practitioners who want to develop social issues within impact assessment, and possibly also to introduce a social impact assessment framework, but with no management or coordination among them. The conclusion is that in the absence of a government initiative to clarify how social impacts can be addressed in transport infrastructure planning, there is a need for an external network for organisations involved in transport infrastructure EISs.